Written Emotional Disclosure Can Promote Athletes’ Mental Health and Performance Readiness During the COVID-19 Pandemic - Davis, Paul A.; Gustafsson, Henrik; Callow, Nichola; Woodman, Tim (Frontiers in Psychology, 2020)
The widespread effects of the COVID-19 pandemic have negatively impacted upon many athletes’ mental health and increased reports of depression as well as symptoms of anxiety. Disruptions to training and competition schedules can induce athletes’ emotional distress, while concomitant government-imposed restrictions (e.g., social isolation, quarantines) reduce the availability of athletes’ social and emotional support. Written Emotional Disclosure has been used extensively in a variety of settings with diverse populations as a means to promote emotional processing. The expressive writing protocol has been used to a limited extent in the context of sport, and predominantly in support of athletes’ emotional processing during injury rehabilitation. We propose that Written Emotional Disclosure offers an evidence-based treatment that can promote athletes’ mental health and support their return to competition. Research exploring the efficacy of the expressive writing protocol highlights a number of theoretical models underpinning the positive effects of Written Emotional Disclosure; we outline how each of these potential mechanisms can address the multidimensional complexity of the challenging circumstances arising from the COVID-19 pandemic (e.g., loss of earnings, returning to training and competition). Considerations and strategies for using Written Emotional Disclosure to support athletes during the COVID-19 pandemic are presented.